The Impact of Tempeh Milk and Soymilk on Adolescent Hemoglobin Level - Ayu Pravita Sari; Putri Yuniarti; Arie Krisnasary (Universitas Airlangga, 2023)
Among Indonesia, there is a 42% of anemia in adolescent girls. Study becomes challenging for those with anemia because blood may not bind oxygen from lungs to the rest of the body effectively. Consume soy and tempeh milk can be alternative treatment for anemia patients. In this study, young girls at SMP Negeri 2 Bengkulu City were tested to see how well tempeh milk and soy milk increased hemoglobin level. This study involved 36 young girls, aged 12 to 14, subjected to two-group pretest and posttest quasi-experimental design. The sample was taken by purposive sampling technique followed inclusion criteria namely, do not have infectious diseases and do not have blood disorders. The first treatment was given 200 mL of tempeh milk and the second treatment was given 200 mL of soy milk for 14 days. The average hemoglobin level of adolescent girls before intervention with tempeh milk is 12.8 g/dL and after the intervention was increased to 14.2 g/dL. The average hemoglobin level of adolescent girls before intervention with soy milk was 12.7 g/dL and after the intervention was increased to 13.7 g/dL. Tempeh milk and soy milk had the same effectiveness in increasing hemoglobin levels of adolescent girls at SMP Negeri 2 Bengkulu City.